Potenciais e produtos geológicos e geomorfológicos na porção Norte do Estado de Roraima para o Geoturismo - Lopes, Rubenita Cruz dos Santos (2019)
The north portion of Roraima state in Brazil integrates Brazilian Northern Border, limited in the North-Northwest by the Bolivarian Republic of Venezuela and in the West by the Cooperative Republic of Guyana. The study area encompasses the municipalities of Normandia, Pacaraima, Uiramutã and part of Amajarí. The region is distinguished by its beauty with landscape geological and geomorphological features with recognized scenic potential nationally and internationally, with remarkable relief features, waterfalls, rapids, erosive features, geological and archeological sites. Such geodiversity has brought us to investigate the landscape of these municipalities, seeking to analyze geological and geomorphological attributes and their geotouristic potential. Therefore, literature research was conducted about the local geodiversity as well as using cartographic data analysis (IBGE, CPRM) and remote sensing images that have been corrected regarding geometry and atmosphere. SPRING, ENVI, ARCgis and SRTM softwares were used to make thematic maps of Denudation, Accumulation and Topographic Profile with escale 1.1.000.000. Field work was conducted seeking to register the geotouristic spots’ GPS location (UTM geographical coordinates), to photograph and to describe the geofeatures. In the same way office work was essential for analysis of the data, classification of geofeatures and making of the thematic maps here presented. Information about the local investments were acquired through government institutions in the state as well as websites. Therfore, we proved the relevance of this rich geodiverse scenery with geotouristic features (geological and geomorphological) that favor the implementation of the activity, with detailed identification of landscape features in each municipality, considering access, indigenous territories, conservation areas, that are obstacles to the research in the region. Besides, verifying the classification of geofeatures and the intrinsic, cultural, aesthetic, scientific and educational values they encompass and the potential use of these areas point to a perfect setting for geotouristic activities such as the Tepequém Ridge that is an important touristic product of the state. However touristic products are not enough without public sector investments, that have shown through our analysis to be incipient. Thus this research brings a significant contribution regarding regional geotourism as well as to assist the expectations of potential use and investments in this field.